2016
DOI: 10.1242/bio.017525
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone signaling induces two phases of cell cycle exit inDrosophilacells

Abstract: During development, cell proliferation and differentiation must be tightly coordinated to ensure proper tissue morphogenesis. Because steroid hormones are central regulators of developmental timing, understanding the links between steroid hormone signaling and cell proliferation is crucial to understanding the molecular basis of morphogenesis. Here we examined the mechanism by which the steroid hormone ecdysone regulates the cell cycle in Drosophila. We find that a cell cycle arrest induced by ecdysone in Dros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 75 publications
(114 reference statements)
4
61
0
Order By: Relevance
“…We reasoned that ecdysone signaling may be involved, since it controls developmental transitions in insects (Thummel 2001;King-Jones and Thummel 2005), and our previous work suggested that an extrinsic signal may coordinate temporal changes in chromatin accessibility between the appendages (McKay and Lieb 2013). We performed RNA-seq at six time points in pupal wings (Guo et al 2016). Consistent with the Ashburner model of ecdysone signaling ( Fig.…”
Section: A Temporal Cascade Of Ecdysone-induced Transcription Factorsmentioning
confidence: 93%
See 4 more Smart Citations
“…We reasoned that ecdysone signaling may be involved, since it controls developmental transitions in insects (Thummel 2001;King-Jones and Thummel 2005), and our previous work suggested that an extrinsic signal may coordinate temporal changes in chromatin accessibility between the appendages (McKay and Lieb 2013). We performed RNA-seq at six time points in pupal wings (Guo et al 2016). Consistent with the Ashburner model of ecdysone signaling ( Fig.…”
Section: A Temporal Cascade Of Ecdysone-induced Transcription Factorsmentioning
confidence: 93%
“…During the next 2 d of pupal development (Fig. 1B, C), cell fates continue to be more finely determined, while the wing undergoes a final round of cell division (Guo et al 2016). This time is also characterized by dramatic morphological changes at both the tissue and cellular levels: Changes in cell shape drive eversion of the wing pouch, and changes in cell adhesion allow the apposed dorsal and ventral surfaces of the wing epithelium to form the upper and lower layers of the wing blade.…”
Section: Gene Expression Is Temporally Dynamic In Pupal Wingsmentioning
confidence: 99%
See 3 more Smart Citations